Kotiate, [3] (1700)
Whale bone kotiate (also called kotiata). Carved beaked figure with hole on butt and round wrist-loop hole. Lobed blade with distinct sinuses and carving at junction of lobes.
Rex Nan Kivell Collection NK11392/7
Part of collection: Maori patus or short weapons.
Also available online
Keywords: Weapons, Maori; Patus -- New Zealand; Weapons